Analisis Kebutuhan dan Karakteristik Penggunaan Google Sites Berbasis AI dalam Pembelajaran Fisika Dasar - Nurul Amalia Aris; Nurvadillah Angraini; Nurhandayani Nurhandayani; Mawardi Jalil Masri; Sulfianty Sulfianty; Juniar Rasyid (Universitas Garut, 2025)
Basic Physics learning for first-year university students still faces various challenges, particularly in understanding abstract and mathematical concepts. This condition highlights the need for interactive and flexible learning media that align with students’ characteristics. This study aims to analyze the needs and usage characteristics of AI-based Google Sites in Basic Physics learning. The research employed a descriptive quantitative approach using a survey method. The participants were first-semester students of the Physics Education and Mathematics education Program at STKIP Darud Da’wah wal Irsyad Pinrang. Data were collected through a needs analysis questionnaire, classroom observations, and limited interviews. The results indicate that more than 80% of students experience difficulties in learning Basic Physics, 78% of respondents reported that lecturers predominantly use textbooks and presentation slides as the main learning media, 82.6% of students agreed or strongly agreed on the need for web-based learning media, and 81% of respondents perceived that AI integration in physics learning media has the potential to help them understand difficult materials. These findings suggest that AI-based Google Sites have strong potential to support Basic Physics learning and can serve as a foundational reference for the development of digital learning media in future studies.